REPREZENTANT DO SPRAW ROSZCZEŃ W ŚWIETLE POLSKICH PRZEPISÓW IMPLEMENTUJĄCYCH IV DYREKTYWĘ W SPRAWIE UBEZPIECZEŃ KOMUNIKACYJNYCH - Orlicka, Justyna (Zeszyty Prawnicze, 2017)
Claims Representative in the Light of Polish Provisions Implementing the Fourth Motor Insurance Directive Summary The Fourth Motor Insurance Directive (Directive 2000/26/EC) has been implemented into Polish law in the provisions of The Compulsory Insurance, Insurance Guarantee Fund and Polish Motor Insurers’ Bureau Act from 22nd May 2003. The paper presents a model of claims representative resulting from the provisions of the above m entioned Act and examines the accuracy of the implementation. W ith that end in view, the paper also gives a brief description of a model of claims representative contained in the provisions of the Directive. The paper discusses the following matters: a deadline for assigning claims representatives, which binds Polish insurance undertakings - a problem resulting from contradictions in the present law; analysis of an obligation to assign claims representatives in order to determine who the Polish legislator may burden with such an obligation - and conclusion that a flagrant exceeding of competence occurred in this field; analysis of an obligation to assign claims representatives, taking into consideration where representatives are to be assigned - and conclusion that the obligation is defined too widely, illogically and exceeds aims set by the Directive; the way the Polish legislator has formed obligations of claims representatives in case an injured party has made a claim - and conclusion that the position of Polish injured parties is worse than a m inim um standard resulting from the Directive.